MECHANICAL PROPERTIES, MORPHOLOGY, AND HYDROLYTIC DEGRADATION BEHAVIOR OF POLYLACTIC ACID / THERMOPLASTIC POLYURETHANE BLENDS - Buys, Yose Fachmi; Ahmad, Mimi Syakina; Anuar, Hazleen; Mahmud, Mudrikah Sofia; Mohd Nasir, Nur Aimi (IIUM Engineering Journal, 2020)
Polylactic acid (PLA) has attracted tremendous interest to be utilized as the replacement for petroleum-based polymers as it possesses good biodegradability, can be derived from renewable sources, and shows high mechanical strength. However, its inherent brittleness and low toughness has limited its usage in broader applications. In this work, PLA was melt blended with tough thermoplastic polyurethanes (TPU) in order to produce eco-friendly polymeric materials with balanced mechanical properties. Moreover, the miscibility and the hydrolytic degradation behaviour of PLA/TPU blends were also investigated as it is important to control material degradation behaviour in some applications. Five compositions of specimens, i.e. neat PLA, PLA/TPU 75/25 vol%, PLA/TPU 50/50 vol%, PLA/TPU 25/75 vol%, and neat TPU, were prepared by melt blending PLA with TPU using an internal mixer, followed by compression moulding. Tensile and impact tests were performed to evaluate the mechanical properties. From the tests, it was apparent that the elongation-at-break and impact strength of the blends increased as the TPU content increased. Dynamic Mechanical Analysis (DMA) and Scanning Electron Microscopy (SEM) observation were conducted to evaluate the miscibility of PLA/TPU blends. DMA results of the blends revealed two tangent delta peaks, indicating that the blends were immiscible, and the SEM micrographs supported this trend. Finally, hydrolytic degradation behaviour of PLA, TPU and PLA/TPU blends was investigated by measuring the weight loss after immersion of the specimens in alkaline solution at a predetermined time, i.e. every 24 hours for up to 8 days. It was found that the degradation behaviour is affected by blend composition, where PLA/TPU 50/50 vol% showed the fastest degradation rate. This result might be ascribed to the co-continuous morphology shown in the PLA/TPU blend 50/50 vol%. ABSTRAK: Polilaktik asid (PLA) telah menarik banyak minat untuk digunakan sebagai pengganti polimer berasaskan petroleum, kerana ia mempunyai biodegradabiliti yang baik, boleh diperolehi daripada sumber yang boleh diperbaharui, dan mempunyai kekuatan mekanikal yang tinggi. Walau bagaimanapun, kerapuhan dan keliatannya yang rendah telah menghadkan penggunaannya dalam aplikasi yang lebih luas. Dalam kajian ini, leburan PLA dicampurkan dengan poliuretan thermoplastik (TPU) bagi menghasilkan bahan polimer yang mesra alam beserta dengan sifat-sifat mekanikal yang seimbang. Selain itu, daya kebolehcampuran dan degradasi hidrolitik daripada campuran PLA/ TPU juga telah dikaji kerana bagi sesetengah aplikasi, faktor degradasi adalah sangat penting. Bagi menghasilkan lima komposisi sampel, iaitu PLA tulen, PLA/TPU 75/25 vol%, PLA/TPU 50/50 vol%, PLA/TPU 25/75 vol%, dan TPU tulen, PLA dan TPU telah dicairkan dan diadun menggunakan mesin pencampur internal, diikuti dengan kaedah pengacuan kompresi. Untuk mengkaji sifat-sifat mekanikal, ujian regangan dan impak telah dijalankan. Hasil ujian tersebut menunjukkan peningkatan nilai pemanjangan pada titik putus dan kekuatan impak, seiring dengan peningkatan komposisi TPU. Manakala, penilaian daya kebolehcampuran diantara PLA dan TPU dijalankan menggunakan analisis mekanikal dinamik (DMA) dan mikroskop pengimbas elektron (SEM). Keputusan DMA, hasil daripada campuran tersebut mendedahkan dua puncak tangen delta, menunjukkan bahawa dua campuran tersebut tidak memiliki daya bolehcampur yang baik. Kesimpulan ini disokong pula oleh gambar mikro dari hasil ujian SEM. Akhir sekali, degradasi hidrolitik PLA, TPU dan campuran PLA/TPU dikaji melalui pengukuran berat sampel setelah direndam di dalam larutan alkali pada masa yang ditetapkan, iaitu setiap 24 jam sehingga 8 hari. Hasil daripada ujian tersebut mendapati degradasi hidrolitik dipengaruhi oleh komposisi campuran. Campuran PLA/TPU dengan komposisi 50/50 vol% menunjukkan kadar penurunan berat yang paling cepat. Hasil ujian ini mungkin boleh dikaitkan dengan sifat morfologi co-continuous yang ditunjukkan dalam campuran PLA/TPU 50/50 vol%.